Aventuras formativas para o ensino de história e cultura africana e afro-brasileira através do roleplaying game - Rodrigues, Joycimara de Morais (2022)
The teaching of African and Afro-Brazilian History and Culture became mandatory after the implementation of Law 10.639/03, becoming a landmark for affirmative actions to combat racism and social exclusion of the black population. However, Africanities continue to be silenced within school curricula or relegated to specific projects that sometimes only repeat stereotypes and perpetuate racist thoughts. This work aimed to identify the contributions of the Roleplaying Game (RPG) as a sensitive mediator in the training of teachers for the teaching of African and Afro-Brazilian History and Culture. The proposal was to use the playfulness of the game, its collaborative, cooperative and playful experience on the proposed theme, in the formation of History teachers of the municipal education network in the city of São Gonçalo do Amarante/RN. This work was composed of five parts, the first being the Introduction, where it presented the theme, objectives and trajectory of the theme. In the second part, there was an approach to the methodological aspects that guided the research, such as the concept of collaborative research and action research. Afterwards, there was talk about the developments brought by the RPG as a sensitive mediator within the research, the characterization of the subjects and the way it was conducted. In the third part, the categories of analysis were addressed, these being the notions of belonging, ancestry and whiteness. The social construction of the image of black people in Brazilian society was presented through discussions on the development of European coloniality thinking, in addition to the debate on African and AfroBrazilian History and Culture, where affirmative actions in the field of History teaching for the implementation of Law 10.639/03 and the importance of thinking about teacher training in a decolonial perspective. In the fourth part, we talked about the developments of the research brought by the RPG as a sensitive mediator, the characterization of the subjects and the way in which it was conducted, approaching topics such as the teacher training of teachers in Teaching and History and Culture. African and Afro-Brazilian previous to the research, diverse historical themes through study meetings and game sessions and how this affected the teachers' practice. After the game sessions, the teachers felt more connected to the theme of Africanities as they had emerged in the theme during the creation of their characters and game. After that, meetings between teachers and students took place when the teachers applied the same methodology with their students and developed their narratives in the proposed scenarios, contributing to a better knowledge on the subject. Finally, it ended with the conclusions, where it was noticed that the teachers were benefited with the teacher training from the RPG because it contributed as a sensitive mediator, insofar as it impelled the teacher to research/immerse more than if they did. to prepare a class on the topic, it approached them with the theme in an empathic way, in addition to helping to give meaning to the knowledge on the topic and taking their experiences as affirmative actions for their teaching practice.